CacyBP/SIP inhibits the migration and invasion behaviors of glioblastoma cells through activating Siah1 mediated ubiquitination and degradation of cytoplasmic p27. (15th November 2017) - Yan, Shiwei; Li, Aimin; Liu, Yuguang
Abstract: Calcyclin‐binding protein or Siah‐1‐interacting protein (CacyBP/SIP) has been reported to be up‐regulated and plays an important role in promoting cell proliferation in human glioma. However, the effect of CacyBP/SIP on glioma cell motility is still unclear. Here, to our surprise, CacyBP/SIP was found to inhibit the migration and invasion of glioma cells U251 and U87. Silencing of CacyBP/SIP significantly promoted the migration and invasion behaviors of glioma cells. On the contrary, overexpression of CacyBP/SIP obviously suppressed them. Further investigation indicated that silencing of CacyBP/SIP significantly reduced the interaction between Siah1 and cytoplasmic p27, which in turn attenuated the ubiquitination and degradation of cytoplasmic p27. In contrast, overexpression of CacyBP/SIP promoted the interaction between Siah1 and cytoplasmic p27, which in turn increased the ubiquitination and degradation of cytoplasmic p27. Importantly, the degradation of p27 could be blocked by Siah1 knockdown. Finally, we found that CacyBP/SIP was reversely related to cytoplasmic p27 in human normal brain tissues and glioma tissues. Taken together, these results suggest that CacyBP/SIP plays an important role in inhibiting glioma cell migration and invasion through promoting the degradation of cytoplasmic p27.